Synthesis of disulphide-Schiff base derivatives and investigations of in vitro antimicrobial activities against some human pathogens - (:unkn) unknown (SCIENDO, 2017)
Thio-Schiff bases are becoming increasingly widespread in various branches such as the preparation of certain medicines, cosmetic products, and polymer production. In particular, the presence of antibacterial, antifungal, antiviral, antitumor and antimalarial properties of Schiff bases containing sulfur in the structure has made these compounds attractive in different disciplines. In this study, different derivatives of dimeric disulfide-Schiff bases have been synthesized. The antibacterial and antifungal activities of the synthesized these compounds were investigated in vitro against some human pathogens (Acinetobacter baumannii, Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus and Candida albicans, C. tropicalis, C. guilliermondii and C. glabrata). Test microorganisms were isolated from the patients appyling to Medical Faculty Hospital of Duzce University were used. Diffusion method was used to determine the antimicrobial activities of the compounds. standard antibacterial (Cefotaxime, Amoxicillin/clavulanicacid) and antifungal (Posaconazole) antibiotics were used as the control group and the results were compared. The result indicated that antimicrobial activity of Disulphide-Schiff Base Derivatives exhibited less activity against bacteria as compared to AMC30 (Amoxicillin/clavulanicacid), but highly effective against bacteria as compared to CTX30 (Cefotaxime). In addition, the compounds exhibited less activity against yeast.